2021
DOI: 10.1109/taffc.2018.2877986
|View full text |Cite
|
Sign up to set email alerts
|

On the Influence of Affect in EEG-Based Subject Identification

Abstract: Biometric signals have been extensively used for user identification and authentication due to their inherent characteristics that are unique to each person. The variation exhibited between the brain signals (EEG) of different people makes such signals especially suitable for biometric user identification. However, the characteristics of these signals are also influenced by the user's current condition, including his/her affective state. In this paper, we analyze the significance of the affect-related componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 47 publications
2
37
0
Order By: Relevance
“…Results using different EEG features and classification methods showed that EEG recordings referring to similar emotional states provided consistently higher identification accuracy than recordings referring to different emotional states, independently of the features, classification method, and signal acquisition session. Furthermore, the use in this work of a portable low-cost off-the-shelf EEG device [16], in contrast to the medical-grade EEG devices used in [5], shows that our finding is also valid for EEG devices with a lower spatial resolution (less electrodes).…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations
“…Results using different EEG features and classification methods showed that EEG recordings referring to similar emotional states provided consistently higher identification accuracy than recordings referring to different emotional states, independently of the features, classification method, and signal acquisition session. Furthermore, the use in this work of a portable low-cost off-the-shelf EEG device [16], in contrast to the medical-grade EEG devices used in [5], shows that our finding is also valid for EEG devices with a lower spatial resolution (less electrodes).…”
Section: Introductionmentioning
confidence: 52%
“…Nevertheless, EEG-based biometrics pose new challenges, such as the problem of permanence of the recorded signals, i.e. finding patterns that are not heavily affected by template ageing, and the problem of defining suitable signal acquisition protocols in relation to the stimuli and the devices used [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Longitudinal studies also confirm the feasibility of EEG as an alternative means of biometrics [3][4][5]. However, one recent study demonstrates different affective mental states potentially influencing stability of EEG as a tool for user identification [6]. As such, discriminative EEG biometric feature extractor models that can filter out specific nuisance variables are likely to enhance usability of generated invariant features for biometric identification.…”
Section: Introductionmentioning
confidence: 87%